Relationship between Personality Traits and Nicotine Dependence in Male and Female Smokers of African-American and European-American Samples - Choi, Jung-Seok; Payne, Thomas J.; Ma, Jennie Z.; Li, Ming D. (Frontiers in Psychiatry, 2017)
Aims: Personality characteristics are linked to nicotine dependence (ND). It remains unclear whether these factors differ across African-American (AA) and European-American (EA) male and female smokers. This study was aimed to determine the relationship between personality traits and smoking status, as well as the degree of ND, in AA and EA male and female samples. Methods: A total of 5,040 participants (AA: N=3,737, female=54.31%; EA: N=1,313, female=64.51%) were included in this study, with 2,474 smokers and 2,566 nonsmokers. The measures used in this study included: five dimensions of personality by the NEO Personality Inventory-Revised (neuroticism, extraversion, agreeableness, openness to experience, and conscientiousness), Fagerström Test for ND (FTND), and Drive subscale of the ND Syndrome Scale (NDSS). Results: In the AA sample, Neuroticism was significantly associated with a higher risk of smoking (odds ratio (OR)=1.057; 95% confidence interval [CI] 1.032, 1.083; p<0.0001), and Conscientiousness was significantly associated with decreased risk of smoking (OR =0.936; 95% CI 0.912, 0.961; p<0.0001). In the EA sample, higher Neuroticism was associated with increased risk of being a current smoker (OR=1.058; 95% CI 1.013,1.104; p=0.0105). Further, we found that a lower level of Neuroticism and higher level of Conscientiousness were associated with the severity of ND in both the AA and EA samples and a broader range of personality factors were involved in predicting the severity of ND in the AA samples. However, no differential association was detected between male and female smokers of both AA and EA samples. Conclusions: There exist differential relationships between personality traits and the severity of ND in the AA and EA samples.